COBRAMM 2.0 A software interface for tailoring molecular electronic structure calculations and running nanoscale (QM/MM) simulations - Weingart,O; Nenov,A; Altoe,P; Rivalta,I; Segarra-Marti,J; Dokukina,I; Garavelli,M (Journal of Molecular Modeling, 2018)
We present a new version of the simulation software COBRAMM, a program package interfacing widely known commercial and academic software for molecular modeling. It allows a problem-driven tailoring of computational chemistry simulations with effortless ground and excited-state electronic structure computations. Calculations can be executed within a pure QM or combined quantum mechanical/molecular mechanical (QM/MM) framework, bridging from the atomistic to the nanoscale. The user can perform all necessary steps to simulate ground state and photoreactions in vacuum, complex biopolymer, or solvent environments. Starting from ground-state optimization, reaction path computations, initial conditions sampling, spectroscopy simulation, and photodynamics with deactivation events, COBRAMM is designed to assist in characterization and analysis of complex molecular materials and their properties. Interpretation of recorded spectra range from steady-state to time-resolved measurements. Various tools help the user to set up the system of interest and analyze the results.